2020
DOI: 10.1002/adfm.201910214
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Instability Control of 1D Nanowire Networks for a Large‐Area Stretchable and Transparent Electrode

Abstract: A commonly used strategy to impose deformability on conductive materials is the prestrain method, in which conductive materials are placed on prestretched elastic substrates and relaxed to create wavy or wrinkled structures. However, 1D metallic nanowire (NW) networks typically result in out-of-plane buckling defects and NW fractures, due to their rigid and brittle nature and nonuniform load transfer to specific points of NW. To resolve these problems, an alternative method is proposed to control the elastic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 67 publications
2
40
0
Order By: Relevance
“…Figure 2C shows the sheet resistance versus the mechanical stretchability. With a combination of stretchability and conductivity, the NHSE in this work is superior to the most recently reported composite‐based stretchable electrodes, 22,24,38–44 including LM‐elastomer composite (e.g., Fe‐LM and Ag‐LM) and Au‐LM composites (e.g., Ag flakes, Ag NWs, and conductive polymers).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 2C shows the sheet resistance versus the mechanical stretchability. With a combination of stretchability and conductivity, the NHSE in this work is superior to the most recently reported composite‐based stretchable electrodes, 22,24,38–44 including LM‐elastomer composite (e.g., Fe‐LM and Ag‐LM) and Au‐LM composites (e.g., Ag flakes, Ag NWs, and conductive polymers).…”
Section: Resultsmentioning
confidence: 74%
“…This can also be explained by micro-wrinkles, which have been known for mitigating effective strain applied on stretchable devices. 45,46 In addition, the resistance varied by ~12% after the cycles, making the NHSE among the most robust electrodes in recent state-of-theart works 34,36,43,44,[47][48][49][50] (Figure 2E, Movie S1, Tables S1 and S2). Moreover, the normalized electrical resistance changes merely against twisting, bending, and 25 000-bending cycles, as shown in Figure S8.…”
Section: Electrical Characterization Of the Nhse Under Mechanical And...mentioning
confidence: 99%
“…Copper-doped zinc sulfide (ZnS:Cu) in the phosphor layer has excellent chemical stability and electroluminescence properties. In particular, ZnS as the primary material while Cu as the luminescent element in the center emits green or blue light upon excitation [29][30][31][32][33]. Emission materials can be easily tuned using doping with different concentrations and types of elements; incorporating and co-doping with different transition metals is an important way to prepare inorganic luminescent materials.…”
Section: Bio-inspired Electroluminescent Skinmentioning
confidence: 99%
“…Electrically conductive materials in the form of nanowires (molybdenum, copper, nickel, gold, silver, or palladium [ 99 ]) can be used to fabricate E-skin sensors; their conductivity is in the order Ag > Cu > Au. Studies of E-skin sensors comprising metal nanowires with high conductivity and transparency are underway [ 100 ].…”
Section: Classification Of Materialsmentioning
confidence: 99%
“…Sun et al [ 95 ] reported that the conductivity of silver nanowires at room temperature was similar to that of bulk silver . Silver nanowires are used to manufacture flexible transparent electrodes because of their high thermal/electrical conductivity and chemical stability [ 100 ]. Silver nanowires can be created by an oxidation–reduction process and template-directed synthesis, which includes chemical/electrochemical vapor deposition.…”
Section: Classification Of Materialsmentioning
confidence: 99%